Alcoholism among Tribals: A Psycho-Social Study: Exploring the prevalence and impact of alcoholism among tribal communities (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Alcoholism has become an acute problem in the society, particularly at its peak, in the tribal community. It become a part and parcel of their traditions and conventions. Today many families are suffering from chronic and incurable diseases. They cannot afford medical treatment due to poverty. They become helpless. It create depression among many adults. The researcher selected 100 male tribal and 100 female tribals randomly from different Taluka in Sabarkantha and Banasakantha district. All the subject having drinking experience and also use to drink during study period. Spencer Rathun's (1995) test was selected for the study. There is no significant difference between male 'adivasis' and female 'adivasis' in relation to the factors as group action (pleasure expression), social reward, celebration, religious functions and habit. The degree of alchoholism is found more in male tribals as compared to female tribals.